Perbedaan Perubahan Kondisi Gulma Rumput Pahit (Axonopus compressus) pada Aplikasi Herbisida Sistemik dan Kontak - Vira Irma Sari (JURNAL CITRA WIDYA EDUKASI, 2020)
Systemic and contact herbicides have a difference in the time it takes to kill weeds. The objectives of this experiment were to know time of change and physic condition of Axonopus compressus after systemic and contact herbicides application. This research conducted at Teaching Farm 2 Politeknik Citra Widya Edukasi on November – December 2019. This research was arranged in a non factorial completely random design with two treatments, A1 (Systemic herbicide) and A2 (Contact herbicide). Systemic herbicide using Glifosat 1%, and contact using Paraquat dichlorida 1%. Each of treatments repeated three times, so that there were 6 experimental unit. The data was analysis of variance and LSD Test. The result of this research are application of systemic and contact herbicides siginifficanty affected to time of change and physic condition of Axonopus compressus. The fastest change time and highest physical condition score is in contact herbicide treatment, and significantly different with systemic herbicide. Systemic herbicides inhibit the growth of weeds by entering the tissues, whereas contact only affects the affected part.